MORAL JUDGEMENT DISCUSSION GROUPS -: IDIOSYNCRASIES OF THE BRAZILIAN CASE - M. B. Biaggio, Angela (2012)
This paper describes a series of studies in which Kohlbergand Blatt's group discussion technique was utilized with the purpose ofraising maturity of moral judgement. Subjects in Study I were 31 eighthgradersof both sexes who showed significant gains from pre-test topost-test. Study II has as subjects Education undergraduate studentswho also showed gains in moral maturity. The most striking resultswere a case of serendipity: Brazilian adolescents generally do not liketo discuss dilemmas brought by the experimenter or group discussioncoordinator. An attempt was made to elaborate a set of locallyrelevantdilemmas after participating in the group discussions and after learningthe basics of Kohlberg's theory. Three of these dilemmas are reportedin full, for illustrative purposes.The reluctance to accept ready-made dilemmas is discussed interms of previous findings of low incidence of Stage IV thinking amongBrazilians. The need for adaptation of the moral discussion techniqueand analogous ones is emphasized.